Economical and Practical Strategies for Synthesis of a-Trifluoromethylated Amines - Jiang, C.J.; Cheng, C.L.; Yuan, S.F. (Asian Journal of Chemistry, 2015)
A powerful approach to synthesize a-trifluoromethylated amines has been developed. The method is operationally simple, broad in substrate scope and amenable to scale-up using trifluoroacetic anhydride. Meanwhile, the strategy not only provided a versatile approach to synthesize a-trifluoromethylated amines but also provides a new method for exploring the new reactivity of trifluoroacetic anhydride.